Analysing Resistance Elements in the Poems of Maya Angelou (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
African American poet and memoirist Maya Angelou (1928–2014) is well renowned for her autobiographical book I Know Why the Caged Bird Sings and her lengthy poem "On the Pulse of Morning," which she recited during President Bill Clinton's inauguration in 1993. As a modern-day Black writer, she distinctively blends personal experience, cultural understanding, and cultural awareness into her artwork on a regular basis. African American themes of self-discovery, progress, and survival are explored in her poetry. Angelou is motivated to eliminate the division between dominant and subaltern cultures and reform the cultural hierarchy because to the suffering that White Anglo-Saxon Protestant (WASP) culture, the hegemonic culture, has done upon African Americans.